The Effect of Brand Image, Product Quality, and Halal Labeling on Junkfood Product Purchase Decision (Case Study of FEB Students of Universitas Muhammadiyah Surakarta) - Trisno, Rafi; Nasir, Moechammad (Majapahit Journal of Islamic Finance and Management, 2025)
This study explores the influence of Brand Image, Product Quality, and Halal Labeling on the purchase decisions of junk food products among students of the Faculty of Economics and Business at Universitas Muhammadiyah Surakarta. Using a quantitative approach, data were obtained from 150 purposively selected active consumers through structured questionnaires with a 5-point Likert scale. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Brand Image and Product Quality significantly and positively influence purchase decisions, indicating that favorable brand perception and perceived quality drive student preferences for junk food. Conversely, Halal Labeling does not show a significant effect, despite the predominantly Muslim student population. This surprising result suggests a possible shift in consumer priorities or limited awareness of halal concepts, warranting further qualitative research. Methodologically, the use of PLS-SEM is appropriate; however, the sample’s restriction to one faculty and purposive selection limits generalizability. The study provides valuable insights for marketers to improve product appeal while maintaining halal certification. Future research should broaden the sample scope, include additional variables such as price and promotion, and consider mixed-method approaches to deepen understanding of consumer behavior.